A Search for QPOs in the Blazar OJ287: Preliminary Results from the 2015/2016 Observing Campaign - Zola, S.; Valtonen, M.; Bhatta, G.; Goyal, A.; Debski, B.; Baran, A.; Krzesinski, J.; Siwak, M.; Ciprini, S.; Gopakumar, A.; Jermak, H.; Nilsson, K.; et al. (Galaxies, 2016)
We analyse the light curve in the R band of the blazar OJ287, gathered during the 2015/2016 observing season. We did a search for quasi-periodic oscillations (QPOs) using several methods over a wide range of timescales. No statistically significant periods were found in the high-frequency domain both in the ground-based data and in Kepler observations. In the longer-period domain, the Lomb-Scargle periodogram revealed several peaks above the 99% significance level. The longest one—about 95 days—corresponds to the innermost stable circular orbit (ISCO) period of the more massive black hole. The 43-day period could be an alias, or it can be attributed to accretion in the form of a two-armed spiral wave.